2016
DOI: 10.1016/j.jmps.2016.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Localized bulging in an inflated cylindrical tube of arbitrary thickness – the effect of bending stiffness

Abstract: We study localized bulging of a cylindrical hyperelastic tube of arbitrary thickness when it is subjected to the combined action of inflation and axial extension. It is shown that with the internal pressure P and resultant axial force F viewed as functions of the azimuthal stretch on the inner surface and the axial stretch, the bifurcation condition for the initiation of a localized bulge is that the Jacobian of the vector function (P, F ) should vanish. This is established using the dynamical systems theory b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 39 publications
2
99
0
Order By: Relevance
“…We emphasize that this correspondence is lost when, for instance, it is the λ z that is held fixed in rotating the tube. Drawing upon the results of [Fu et al 2016], we may then further conjecture that when the inner surface is traction-free or subjected to a hydrostatic pressure P the bifurcation condition for localized bulging is simply J ( , F) = 0, whether it is the F or λ z that is fixed in rotating the tube. We shall verify in the next section that this is indeed the case.…”
Section: Primary Deformationmentioning
confidence: 95%
See 3 more Smart Citations
“…We emphasize that this correspondence is lost when, for instance, it is the λ z that is held fixed in rotating the tube. Drawing upon the results of [Fu et al 2016], we may then further conjecture that when the inner surface is traction-free or subjected to a hydrostatic pressure P the bifurcation condition for localized bulging is simply J ( , F) = 0, whether it is the F or λ z that is fixed in rotating the tube. We shall verify in the next section that this is indeed the case.…”
Section: Primary Deformationmentioning
confidence: 95%
“…However, it can be shown that this Jacobian is a nonzero multiple of J ( , F) when the connection (2-10) is used. The case previously studied by [Fu et al 2016] can now be viewed as a special case, corresponding to ≡ 0, of the current more general formulation. The observations made in that paper about J ( P, F) can be extended to the case when is nonzero but is held fixed.…”
Section: Primary Deformationmentioning
confidence: 99%
See 2 more Smart Citations
“…If the geometric nonlinearity is not taken into account then P b = P bs = −Dr and the bending pressure is included only in the equation for r. Only the term −br is added to the left part in this A non-differential term related with the latitudinal (circular) bending resistance [8] may be included in pressure formula. But if the wall of the tube is weakly stretched (this is a typical case when inclusion of meridional bending resistance is required) or if h/R is close to zero this term vanishes.…”
Section: Main Generalizations and Simplification Of The Modelmentioning
confidence: 99%